Enhancing Food Security in the face of Climate Change - CGIAR Research Program on Climate Change, Agriculture and Food Security (2011)
Presentation by David Radcliffe (European Commission). Filmed at The Conference on Climate Change, Agriculture, and Food Security, 4 May 2010, Nairobi, Kenya